Demontrasi, Pemberian Makan Bayi dan Anak (PMBA) Nasi, Telur, Tahu, Kelor (Nurul), Berbasis Pangan Lokal: Penelitian - Ni Ketut Kariani; Lulu Aulia Moh.Amin; Della Nilasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Infant and Young Child Feeding (PMBA) demonstration in RT 8, Boneoge Village, has not been implemented properly. In Central Sulawesi, specifically in Banawa District, observations indicate 111 cases of stunted toddlers. This community service activity aims to understand and implement local food-based PMBA to accelerate the prevention and reduction of stunting in Boneoge Village. This community service activity through counseling, observation, and question and answer sessions was conducted in August. The study population included 85 toddlers aged 0–59 months. Data collection was conducted through direct interviews with all mothers of toddlers, and data were analyzed using univariate analysis. The results showed that PMBA practices were not age-appropriate, ANC visits during pregnancy were still low, and some toddlers experienced ARI and worm infections. Knowledge of toddler mothers about stunting was also still low (13%). After the activity, participation of toddler mothers increased, although only 11 people (13%) attended. In conclusion, there was an increase in knowledge before and after the counseling regarding complementary feeding (MP-ASI), ANC visits, infectious diseases, worms, ARI, and stunting. PMBA demonstrations help improve mothers' knowledge and skills in preparing complementary foods appropriate to their child's age and foster toddlers' interest and preference for balanced, nutritious food.